Hydrogen Ion Equilibria of Interaction of Ribonucleic Acid and Albumin-Bovine - Pukar Vidyarthi, Ram (Asian Journal of Chemistry, 2010)
On interaction of ribonucleic acid and albumine-bovine the hydrogen ion equilibrium is altered both in aqueous and in 0.25 M KC1 solution. The ± interaction in the protein chain makes the alteration in pH more prominent in salt solution than in aqueous medium. In acid titration this feature is absent Conformational changes are also accompanied with the availabilities of charged sites in the interacting species of the protein and nucleic acid. A structural variation is expected to modulate the translation of conserved RNA in the protein synthesis during the interaction.